2016
DOI: 10.3892/ol.2016.4493
|View full text |Cite
|
Sign up to set email alerts
|

Impact and mechanism of non-steroidal anti-inflammatory drugs combined with chemotherapeutic drugs on human lung cancer-nude mouse transplanted tumors

Abstract: Abstract. The present study aimed to investigate the impact of indomethacin treatment combined with oxaliplatin treatment on the expression of cluster of differentiation 44 variant 6 (CD44v6), matrix metalloproteinase-2 (MMP-2) and survivin in human lung cancer-nude mouse transplanted tumors. The human lung adenocarcinoma (A549)-nude mouse transplanted tumor model was established, and the mice were divided into a control group, an indomethacin treatment group, an oxaliplatin treatment group and an indomethacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
(33 reference statements)
3
3
0
Order By: Relevance
“…It seems, therefore, that oxaliplatin promotes autophagy in these gastric cancer cells and that indomethacin, alone and especially in the presence of chloroquine, inhibits the degradation of the newly formed autophagosomes. When we added indomethacin to the culture media after a period in the presence of oxaliplatin, this NSAID enhanced the toxic effect of oxaliplatin and produced a concomitant decrease in autophagic activity, which may explain the synergy observed between the two drugs in the present study and previously in an in vivo model of cancer 26 . Thus, inhibition of lysosomal function and the consequent interference with autophagic degradation may be partly responsible for the beneficial effects of indomethacin in cancerous processes reported in some studies 4 , 26 , 27 .…”
Section: Discussionsupporting
confidence: 72%
“…It seems, therefore, that oxaliplatin promotes autophagy in these gastric cancer cells and that indomethacin, alone and especially in the presence of chloroquine, inhibits the degradation of the newly formed autophagosomes. When we added indomethacin to the culture media after a period in the presence of oxaliplatin, this NSAID enhanced the toxic effect of oxaliplatin and produced a concomitant decrease in autophagic activity, which may explain the synergy observed between the two drugs in the present study and previously in an in vivo model of cancer 26 . Thus, inhibition of lysosomal function and the consequent interference with autophagic degradation may be partly responsible for the beneficial effects of indomethacin in cancerous processes reported in some studies 4 , 26 , 27 .…”
Section: Discussionsupporting
confidence: 72%
“…The MMP-9 inhibitory activity of prodrug 17 was evaluated by immunohistochemical staining using slices of CT-26 mice tumors in comparison with the effect of oxaliplatin and saline. Compound 17 showed significant inhibition of MMP-9 expression (6.8%), while oxaliplatin inhibition level was 8.1%, in accordance with the literature data [ 41 ]. The observed difference in inhibitory activity is associated with the presence of the naproxen moiety in prodrug 17 .…”
Section: Dual-action Pt(iv) Prodrugs With Nsaid Axial Ligandssupporting
confidence: 89%
“…Among all isoforms, CD44v6 contains a mutation of exon 11 and plays an important role in enhancing the adhesive ability of tumor cells [24]. An evidence-based report showed that an increase in the expression of CD44v6 altered the physiochemical properties of tumor cells and increased their metastatic potential [25]. The present study showed that the expression of CD44v6 protein and mRNA were concentration dependent on VPA, which demonstrated the inhibitory effect of VPA on tumorigenesis.…”
Section: Discussionsupporting
confidence: 56%